La Domesticación de Animales en los Andes - Wing, Elizabeth (1975)
In the western hemisphere the domestication of animals is focused on the Andes. Compared to the Near East, which is another center of domestication, the origin of the Andean is little known. This may be due, in part, to the fact that domesticated animals in South America did not have the economic importance of Old World animals, so their study has not been an urgent problem. However, the Andean center of domestication is an area in which the process of animal domestication can be studied and therefore offers the opportunity to gain a greater understanding of the development of the close relationship that exists between man and domesticated animals.